PENGARUH DEBT TO EQUITY RATIO, RETURN ON ASSET, INVESTMEN OPPORTUNITY SET TERHADAP KEBIJAKAN DIVIDEN PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2015-2017 - Nafiah, Zumrotun; NURHIDAYAH, EVINTA AMALIA (Sekolah Tinggi Ilmu Ekonomi Semarang, 2024)
Dividend policy is very important to determine the portion of profits that will be turned into retained earnings and which will be distributed to shareholders. This research aims to determine the influence of Debt to Equity Ratio, Return On Assets, Investment Opportunity Set on dividend policy in manufacturing companies listed on the Indonesia Stock Exchange for the 2015-2017 period. The population in this study were 149 manufacturing companies listed on the Indonesia Stock Exchange for the 2015-2017 period. The sample was taken using purposive sampling, and 28 companies were obtained. The data obtained is secondary data using the documentation method. Testing the classical assumptions used in this research is using the normality test, multicollinearity test, heteroscedasticity test, and autocorrelation test. Hypothesis testing in this research uses multiple regression analysis techniques. The variables in this research are Debt to Equity Ratio (DER), Return On Assets (ROA), Investment Opportunity Set (IOS) and Dividend Policy. The results of this research are (1) Debt to Equity Ratio has a significant effect on dividend policy, this is shown by a significance value of 0.014 < 0.05 (2) Return On Assets has a significant effect on dividend policy, this is shown by a significance value of 0.017 < 0.05 (3) Investment Opportunity Set has a significant effect on dividend policy, this is proven by a significance value of 0.03 < 0.05.